Comparative genomics for understanding the structure, function and sub-cellular localization of hypothetical proteins in Thermanerovibrio acidaminovorans DSM 6589 (tai). (April 2016) - Thakare, Hitesh S.; Meshram, Dilip B.; Jangam, Chandrakant M.; Labhasetwar, Pawan; Roychoudhary, Kunal; Ingle, Arun B.
Graphical abstract: Abstract: The Thermanerovibrio acidaminovorans DSM 6589 (tai) is a unique bacterium isolated from anaerobic sludge bed reactor from sugar refinery in Netherland. The comparative genomic studies for understanding the hypothetical proteins in T. acidaminovorans DSM 6589 (tai) were carried out using different bioinformatic tools and web servers. In all 320 hypothetical proteins were screened from the total available genome. The Insilico function prediction for 320 hypothetical proteins was achieved by using different online servers like CDD-Blast, Interproscan and pfam whereas, the structure prediction for 202 hypothetical proteins were deciphered by using protein structure prediction server (PS2 server). The sub-cellular localization for the identified proteins was predicted by the use of cello v2.5 for 320. The study carried out has helped us to understand the structures and functions of unknown proteins available in T. acidaminovorans DSM 6589 (tai) through comparative genomic approach.